Factors Influencing Career Choices of Dental Students in a State University in Turkey - YARAT, AYŞEN; AKYÜZ, SERAP HATİCE (MARMARA UNIV, INST HEALTH SCIENCES, 2018)
Objective: The aim of this study was to investigate the factors influencing the career choices of students in Marmara University Faculty of Dentistry in the 2014-2015 academic year. Methods: Data were collected from 468 dental students by using a 55-item questionnaire. Results: Mean age of students were 21.6 (range 17-25); 300(64.1%) of them were female and 168(35.9%) were male. Two hundred two (43.2%) students indicated that their first choice was dentistry. If they were to make a choice for a second time, 196(41.9%) of students would again prefer dentistry as their career. There was a significant difference between the year of study and the statement I will prefer dentistry again (p<0.05). In fact, 45(49.5%) of first-year students claimed that they would choose dentistry again, whereas 35(41.7%) of fifth-year students stated the opposite. As being passed to higher classes, the percentage of students who will prefer dentistry again decreased. One hundred forty one (30.1%) of all students reported wanting to change their career. It was stated as reasons for changing careers that being a dental student was stressful. Students were most influenced by their family (61.4%). Four hundred eight (87.2%) students were determined to choose dentistry because of its high income. 399 (85.2%) students stated that dentistry is a prestigious profession and this criterion was significant in their career choices. Conclusion: The majority of students who preferred Marmara University, Faculty of Dentistry were girls, and there were many factors influence the career choices and future plans of the students, with the most important beings were the families, the high income level and the prestige of the profession.
Keywords: Career choice; Dentistry; Students; Questionnaire; DENTISTRY; PERCEPTIONS; MOTIVATION; ATTITUDES; PROFILE; FUTURE